The CEFR Companion Volume: Opportunities and challenges for language assessment - Benjamin Kremmel; Kathrin Eberharter; Eva Konrad; Elisa Guggenbichler; Doris Moser-Frötscher; Viktoria Ebner; Carol Spöttl (DiSlaw, 2024)
Over the last two decades, the Common European Framework of Reference for languages (CEFR) has become the most influential tool of language policy-making in Europe and beyond. The publication of the companion volume (CEFR-CV) constitutes a new milestone for teaching, learning and assessing languages, and is a most timely reaction to common criticism of the framework. In addition to new scales, descriptors and competence levels, the CEFR-CV introduces new modalities and broadens the scope for mediation and plurilingual/cultural communication, thereby updating and extending previous construct definitions for increasingly digitized and diverse societies. Despite the CEFR’s major impact on the language testing industry, there is thus far scarce literature on how to operationalize the CEFR-CV for assessment with the expanded framework. In addition to the huge potential for innovative assessment tasks and formats, this raises questions with regard to construct definitions, task development, test quality assurance, and rating practices. This paper will focus on six noteworthy innovations of the CEFR-CV and discuss the opportunities and challenges for assessment: (1) departure from the native-speaker norm, (2) stronger consideration of digital communication, (3) interlingual mediation, (4) intralingual mediation, (5) phonological awareness, and (6) the provision of richer descriptions of lower-level learner competencies.